Positive electrode active material for lithium secondary battery, lithium secondary battery comprising same, and method for preparing positive electrode active material for lithium secondary battery
By forming a uniform lithium phosphate compound coating on the surface of the nuclear particles of the lithium secondary battery, the stability problem when the positive electrode active substance comes into contact with the solid electrolyte is solved, the ionic conductivity and electrochemical stability are improved, and the performance of the battery is improved.
Patent Information
- Application Number
- CN202380085581.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-14
- Filing Date
- 2023-06-15
- Publication Date
- 2025-07-22
AI Technical Summary
When the positive electrode active substance of the existing lithium secondary battery comes into contact with the solid electrolyte, there are problems of insufficient ionic conductivity and electrochemical stability, resulting in unstable reactions and high internal resistance.
A lithium phosphate compound coating with uniform thickness is formed on the surface of the nuclear particles. The positive electrode active material is prepared by using different types of solvents that are insoluble, ensuring that the difference between the maximum thickness and the minimum thickness of the coating is below 17 nm. The coating contains lithium phosphate compounds of transition metals such as titanium and other metals.
It improves the ionic conductivity and electrochemical stability of the positive electrode active substance, reduces the interface resistance, enhances the reaction stability and structural stability, and improves the life and high-rate performance of lithium secondary batteries.
Smart Images

Figure CN120359626A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a lithium secondary battery including the same, and a method for preparing the positive electrode active material for a lithium secondary battery. Background Art
[0002] A secondary battery is a battery that can be repeatedly charged and discharged. With the development of the information communication and display industries, secondary batteries are widely used as power sources for portable electronic communication devices such as camcorders, mobile phones, and laptop computers. In addition, in recent years, battery packs including secondary batteries are being developed and used as power sources for eco-friendly vehicles such as hybrid vehicles.
[0003] Examples of secondary batteries include lithium secondary batteries, nickel-cadmium batteries, nickel-metal hydride batteries, etc. Among them, lithium secondary batteries have a high operating voltage and energy density per unit weight, and are advantageous for charging speed and weight reduction. Therefore, research and development are being actively carried out.
[0004] Currently commercialized lithium secondary batteries mainly use liquid electrolytes. Therefore, with sharp environmental changes such as temperature changes and external impacts, there are safety problems such as leakage, explosion, and fire. To solve these problems, attempts are being made to ensure safety and increase energy density by solidifying the electrolyte.
[0005] An all-solid-state battery may include an electrode assembly including a positive electrode, a negative electrode, and an intermediate electrolyte layer, and the all-solid-state battery may further include a separator (separation membrane) between the positive electrode and the negative electrode. The all-solid-state battery may further include an outer packaging material for accommodating the electrode assembly, such as an outer packaging material in the form of a soft pack.
[0006] Lithium metal oxides can be used as positive electrode active materials for all-solid-state batteries. With the expansion of the application range of lithium secondary batteries, longer life, higher capacity, and higher energy density are required. However, when the positive electrode active material comes into physical contact with the solid electrolyte, the reaction stability may be reduced or the electronic conductivity may increase, and high internal resistance caused by contact resistance and overvoltage caused by low ionic conductivity may occur.
[0007] For example, Korean Patent Publication No. 10-2018-0125408 discloses an electrode for an all-solid-state battery and a manufacturing method thereof. Summary of the Invention
[0008] (I) Technical Problems to be Solved
[0009] One technical problem of the present invention is to provide a positive electrode active material having improved ionic conductivity and electrochemical stability.
[0010] One technical problem of the present invention is to provide a method for preparing a cathode active material having improved ionic conductivity and electrochemical stability.
[0011] One technical problem of the present invention is to provide a all-solid-state battery comprising a cathode active material having improved ionic conductivity and electrochemical stability.
[0012] (II) Technical solution
[0013] The cathode active material according to an exemplary embodiment includes a core particle and a coating, the coating is formed on the surface of the core particle, and the coating contains a lithium phosphate compound containing a transition metal. The difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating may be 17 nm or less.
[0014] In some embodiments, the difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating is 0.1 nm to 10 nm.
[0015] In some embodiments, the thickness of the coating is 1 nm to 50 nm.
[0016] In some embodiments, the cathode active material may satisfy the following formula 1.
[0017] [Formula 1]
[0018] (|T M -T E | / T E )×100≤20
[0019] In the formula 1, T E may be the average thickness value of the coating, and T M may be either the maximum thickness or the minimum thickness of the cross-section of the coating.
[0020] In some embodiments, the content of the coating may be 0.1 part by weight to 1 part by weight relative to 100 parts by weight of the core particle.
[0021] In some embodiments, the lithium phosphate compound may contain titanium and other metals different from titanium.
[0022] In some embodiments, the coating may contain a compound represented by the following chemical formula 1.
[0023] [Chemical formula 1]
[0024] Li a (M b+ ) c P d O (a+bc+5d) / 2
[0025] In the chemical formula 1, M may be at least one selected from Ti, B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W, and 0 < a ≤ 5, 1 ≤ b ≤ 5, 1 ≤ c ≤ 5, 0 < d ≤ 8 may be satisfied.
[0026] In one embodiment, the coating may include a compound represented by the following chemical formula 2.
[0027] [Chemical formula 2]
[0028] Li a (Ti e+ ) x (M1 f+ ) y P d O (a+ex+fy+5d) / 2
[0029] In the chemical formula 2, M1 may be at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W, and 0 < a ≤ 5, 1 ≤ e ≤ 4, 1 ≤ f ≤ 5, 0 < x ≤ 1, 0 < y < 5, 1 ≤ x + y ≤ 5, 0 < d ≤ 8 may be satisfied.
[0030] In some embodiments, the average particle diameter (D 50 ) of the core particles may be 1 μm to 12 μm.
[0031] The lithium secondary battery according to an exemplary embodiment may include: a positive electrode including the positive electrode active material and a solid electrolyte as described above; a negative electrode disposed opposite to the positive electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode.
[0032] In the method for preparing a positive electrode active material according to an exemplary embodiment, a first mixture including a lithium precursor, a coating metal precursor, a phosphorus precursor, and a first solvent may be prepared. Thereafter, a second solvent immiscible with the first solvent may be mixed in the first mixture to prepare a second mixture. Thereafter, primary positive electrode active material particles may be added to the second mixture to prepare a precursor solution, and the precursor solution may be heat-treated to form a coating including a lithium phosphate compound on the surface of the primary positive electrode active material particles.
[0033] According to an exemplary embodiment, the lithium precursor, the coating metal precursor, and the phosphorus precursor may be dissolved in the first solvent and not dissolved in the second solvent.
[0034] In some embodiments, the coated metal precursor may include a first coated metal precursor and a second coated metal precursor, and the first coated metal precursor may be a titanium precursor.
[0035] In one embodiment, the lithium phosphate compound may include a compound represented by Chemical Formula 2 below.
[0036] [Chemical Formula 2]
[0037] Li a (Ti e+ ) x (M1 f+ ) y P d O (a+ex+fy+5d) / 2
[0038] In Chemical Formula 1, M1 may be at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W, and 0 < a ≤ 5, 1 ≤ e ≤ 4, 1 ≤ f ≤ 5, 0 < x ≤ 1, 0 < y < 5, 1 ≤ x + y ≤ 5, 0 < d ≤ 8.
[0039] In some embodiments, the difference between the polarity index of the first solvent and the polarity index of the second solvent may be 4 or more.
[0040] In some embodiments, in the precursor solution, the content of the second solvent may be less than the content of the first solvent.
[0041] According to an exemplary embodiment, before heat-treating the precursor solution, a step of ultrasonically treating the precursor solution may be further included.
[0042] In some embodiments, by the step of ultrasonically treating the precursor solution, a first thin film containing the second solvent may be formed on the primary cathode active material, and a second thin film containing the first solvent may be formed on the first thin film.
[0043] In some embodiments, the step of heat-treating the precursor solution may include the following steps: heating the precursor solution to a first temperature to evaporate the second solvent, and then heating to a second temperature higher than the first temperature to evaporate the first solvent.
[0044] For example, the boiling point of the first solvent may be higher than the boiling point of the second solvent. For example, the first temperature may be higher than or equal to the boiling point of the second solvent and lower than the boiling point of the first solvent, and the second temperature may be higher than or equal to the boiling point of the first solvent.
[0045] (III) Advantageous Effects
[0046] The positive electrode active material according to an exemplary embodiment may include a core particle and a coating formed on the surface of the core particle, and the coating includes a lithium phosphate compound. The difference between the maximum thickness and the minimum thickness of the coating may satisfy a specified range. Accordingly, a thin and uniform buffer layer may be formed on the surface of the core particle, and the reaction stability and lithium ion conductivity of the positive electrode active material may be improved.
[0047] The positive electrode active material may be prepared using different types of immiscible solvents. In addition, the different types of solvents may have mutually different boiling points. Accordingly, a uniform coating may be formed on the surface of the core particle without causing physical defects and thermal damage to the core particle. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a process flow diagram for explaining a method for preparing a positive electrode active material according to an exemplary embodiment.
[0049] Figure 2 is a process flow diagram for explaining a method for preparing a positive electrode active material according to an exemplary embodiment.
[0050] Figure 3 and Figure 4 are schematic diagrams for explaining a method for preparing a positive electrode active material according to an exemplary embodiment, respectively.
[0051] Figure 5 is a TEM image of a part of the positive electrode active material particles according to Example 1.
[0052] Figure 6 is a TEM image of a part of the positive electrode active material particles according to Comparative Example 1. DETAILED DESCRIPTION
[0053] According to an exemplary embodiment, there is provided a positive electrode active material including a lithium metal oxide, a positive electrode including the positive electrode active material, and a lithium secondary battery.
[0054] Hereinafter, embodiments of the present invention will be described in detail. However, these are merely exemplary embodiments, and the present invention is not limited to the specific embodiments described exemplarily.
[0055] <Positive Electrode for Lithium Secondary Battery>
[0056] The positive electrode active material for a lithium secondary battery according to an exemplary embodiment (hereinafter, may be simply referred to as "positive electrode active material") may include a core particle and a coating formed on the surface of the core particle.
[0057] The core particles can reversibly intercalate and deintercalate lithium ions and provide positive electrode activity. For example, the core particles can comprise a lithium metal oxide.
[0058] The core particles can comprise one or more compounds selected from lithium cobalt-based oxides, lithium manganese-based oxides, lithium nickel-based oxides, or lithium composite oxides, etc. For example, the core particles can comprise: layered compounds such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2VO7, lithium iron phosphate oxide, etc.
[0059] In one embodiment, the core particles can comprise a compound represented by the following Chemical Formula 3.
[0060] [Chemical Formula 3]
[0061] Li a Ni b M 1-b O2
[0062] In Chemical Formula 3, a can be 0.95 ≤ a ≤ 1.08, b can be b ≥ 0.5, and M can be Na, Mg, Ca, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Co, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Ba, Zr, or a combination thereof.
[0063] In one embodiment, the core particles can comprise nickel (Ni), and can further comprise at least one of cobalt (Co) or manganese (Mn). For example, nickel-cobalt-manganese (NCM)-based lithium oxide can be used as the core particles.
[0064] For example, nickel (Ni) can be provided as a metal related to the capacity of the lithium secondary battery. As the nickel content increases, the capacity and power of the lithium secondary battery can be improved, but when the nickel content is excessively increased, the life, mechanical stability, and electrical stability may be relatively reduced.
[0065] In one embodiment, the conductivity or resistance of the lithium secondary battery can be further improved by cobalt (Co), and the mechanical stability and electrical stability of the lithium secondary battery can be further improved by manganese (Mn).
[0066] The chemical structure represented by Chemical Formula 3 represents the binding relationship contained within the lattice structure or crystal structure of the core particles, and does not exclude other additional elements. For example, M can be provided as the main active element of the core particles. Chemical Formula 3 is provided to represent the binding relationship of the main active element, and it should be understood that Chemical Formula 3 is a formula that includes the introduction and substitution of additional elements.
[0067] In one embodiment, in addition to containing the main active element, an auxiliary element for enhancing the chemical stability of the positive electrode active material or the crystal structure can be further included. The auxiliary element can be mixed into the crystal structure together and form a bond, and it should be understood that this situation is also included within the scope of the chemical structure represented by Chemical Formula 3.
[0068] According to an exemplary embodiment, the coating can contain a lithium phosphate compound.
[0069] By forming a coating containing a lithium phosphate compound on the surface of the core particles, the direct contact between the core particles and the solid electrolyte can be blocked, and side reactions can be inhibited. In addition, an increase in the interfacial resistance due to contact between the core particles can be prevented.
[0070] Therefore, the coating can act as a buffer layer for the core particles, thereby inhibiting damage and defects of the core particles, and improving the reaction stability and structural stability of the positive electrode active material.
[0071] In one embodiment, the lithium phosphate compound can contain transition metals. For example, it can contain Ti, Y, Sc, Zr, V, Nb, Ta, Cr, and W, etc.
[0072] Therefore, the electrochemical stability and reduction potential (redox potential) of the coating can be further improved, and the structural stability of the positive electrode active material can be improved even under high temperature and high voltage driving. In addition, irreversible decomposition of the solid electrolyte due to reaction with the positive electrode active material can be inhibited.
[0073] According to an exemplary embodiment, the difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating can be 17 nm or less. For example, the cross-section of the coating can refer to the two-dimensional plane of the coating observed in a direction perpendicular to the longest diameter direction of the positive electrode active material particles.
[0074] For example, an electron microscope can be used to photograph a cross-section of the positive electrode active material particles to obtain an image. The thickness of the thickest part in the cross-section of the coating is set as the maximum thickness of the coating, and the thickness of the thinnest part in the cross-section of the coating is set as the minimum thickness of the coating. The thickness of the coating can be the vertical distance from the outer surface of the core particles to the outer surface of the coating.
[0075] In one embodiment, the electron microscope can use a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0076] Since the difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating is 17 nm or less, the coating can thinly and uniformly cover the surface of the core particles. Therefore, the stability and efficiency of the positive electrode active material can be improved.
[0077] For example, when the coating is unevenly formed on the surface of the core particles, the thickness deviation of the coating in each region of the positive electrode active material may increase. In this case, in the region where the thick coating is formed, the ionic conductivity may decrease, thereby possibly losing the path for the entry and exit of lithium ions. In addition, side reactions of the core particles may concentrate in the region where the thin coating is formed, so that the deterioration of the positive electrode active material in this region may be concentrated or accelerated. Therefore, the energy density and life characteristics of the positive electrode active material may decrease, and the performance of the secondary battery at high voltage and high rate may deteriorate.
[0078] According to an exemplary embodiment, by adjusting the difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating to 17 nm or less, a thin-thickness coating can be uniformly formed on the entire surface of the core particles. Therefore, constant electrochemical characteristics and reaction stability can be maintained over the entire surface area of the positive electrode active material, and the content of the coating used to cover the core particles can be reduced, thereby improving the energy density of the positive electrode active material.
[0079] In one embodiment, the difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating can be 15 nm or less, 10 nm or less, 8 nm or less, 5 nm or less. For example, the difference between the maximum thickness and the minimum thickness of the coating can be from 0.01 nm to 17 nm or from 0.1 nm to 10 nm.
[0080] In some embodiments, the thickness of the coating can satisfy the following formula 1.
[0081] [Formula 1]
[0082] (|T M -T E | / T E )×100 ≤ 20
[0083] In the formula 1, T E is the average thickness of the coating, which can be the arithmetic mean of the coating thicknesses measured at 20 or more points of the coating using an electron microscope. T M can be the maximum or minimum value among the above-measured coating thicknesses.
[0084] For example, the average thickness (T E ) of the coating can be measured in one or more, three or more, or five or more directions on the cross-section of the positive electrode active material particles using SEM or TEM, and the arithmetic mean of the coating thickness values measured in 20, 30, 50, 100, or 300 or more regions of the measured cross-sectional image. The more the measured cross-sectional images and the measured regions, the higher the measurement accuracy and reliability.
[0085] Therefore, the uniformity of the coating can be further improved, and the initial efficiency and high-rate characteristics of the secondary battery can be further improved. For example, based on the average thickness of the coating, the heights of the protruding portions and the recessed portions can be substantially similar, and high reaction stability and ionic conductivity can be provided over the entire region of the surface of the positive electrode active material particles.
[0086] In one embodiment, in the formula 1, (|T M -T E | / T E )×100 can be 10 or less or 5 or less.
[0087] In some embodiments, the average thickness of the coating can be 5 nm to 30 nm or 10 nm to 20 nm. Within the above range, a thinner and more uniform coating can be formed on the core particles, thereby further preventing an increase in resistance and side reactions of the core particles due to contact between the core particles. Therefore, the efficiency and lifespan of the secondary battery can be further improved.
[0088] In some embodiments, the thickness of the coating can be 1 nm to 50 nm. In the coating formed on the core particles, the thickness of the thinnest part can be 1 nm or more, and the thickness of the thickest part can be 50 nm or less. For example, the thickness of the coating can be 3 nm to 30 nm or 5 nm to 25 nm. Within the above range, the internal resistance and stability of the positive electrode active material can be further improved.
[0089] In some embodiments, the content of the coating can be 0.1 part by weight to 1 part by weight relative to 100 parts by weight of the core particles.
[0090] For example, when the content of the coating is less than the above range, the coating coverage on the core particles may be insufficient. Therefore, since the coating exists on the core particles in the form of, for example, local islands, it may be difficult to achieve uniform coverage. In addition, when the content of the coating exceeds the above range, an overly thick coating may be formed, and the internal resistance of the positive electrode active material may increase.
[0091] In some embodiments, the average particle size (D 50 ) of the core particles may be from 1 μm to 12 μm. In one embodiment, the average particle size of the core particles may be from 2 μm to 12 μm or from 5 μm to 10 μm. The "average particle size (D 50 )" may be the particle size of the particles when the volume fraction in the volume particle size distribution obtained by accumulating the particles in ascending order of particle size is 50%.
[0092] For example, when the average particle size of the core particles is less than the above range, the specific surface area of the particles may increase excessively, which may lead to an increase in side reactions with the electrolyte, and as the fine particles increase, the electrode density and energy density may decrease.
[0093] For example, when the average particle size of the core particles exceeds the above range, as the particle size increases, the migration distance of lithium ions may become longer, and the capacity characteristics and power characteristics of the lithium secondary battery may decrease.
[0094] In one embodiment, the particle size of the core particles may be from 0.1 μm to 30 μm. For example, the particle size of the core particles may be from 1 μm to 20 μm or from 1 μm to 12 μm. Within the above range, the core particles may have high structural stability, and the capacity and energy density of the secondary battery may be further improved. The "particle size" may refer to the longest diameter or the longest diameter of the particles.
[0095] According to an exemplary embodiment, the lithium phosphate compound may have a sodium superionic conductor (NASICON) structure. For example, "NASICON" is an abbreviation for sodium super ion conductor, and examples include Na 1+ x Zr2Si x P 3-x O 12 (for example, Na3Zr2Si2PO 12 or NaZr2(PO4)3, etc.).
[0096] In one embodiment, the lithium phosphate compound may have the same or similar crystal structure as the sodium superionic conductor compound, and may have a structure in which Na in the sodium superionic conductor structure is replaced by Li and part or all of Zr is replaced by other transition metals such as Ti.
[0097] For example, the lithium phosphate compound may have a lattice structure formed by a network of MO6 (M is a metal such as Ti) octahedra connected by PO4 tetrahedra, and Li ions may occupy sites within the interstitial spaces of the lattice structure. Therefore, due to the transition of lithium ions between the interstitial sites of adjacent lattices, high ionic conductivity can be ensured. In addition, the sodium superionic conductor type lithium phosphate compound has low electronic conductivity, a wide electrochemical window, and high voltage stability, thereby further improving the capacity characteristics and life characteristics of secondary batteries.
[0098] The metal (M) may include, for example, Ti, B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, W, or a combination thereof. In one embodiment, the metal (M) may include Ti.
[0099] According to an exemplary embodiment, the lithium phosphate compound may be represented by the following Chemical Formula 1.
[0100] [Chemical Formula 1]
[0101] Li a (M b+ ) c P d O (a+bc+5d) / 2
[0102] In Chemical Formula 1, M may be at least one metal element selected from Ti, B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W. For example, M may include Ti.
[0103] In Chemical Formula 1, a may be 0 < a ≤ 5, c may be 1 ≤ c ≤ 5, and d may be 0 < d ≤ 8. b is an integer representing the oxidation state of M, and b may be 1 ≤ b ≤ 5.
[0104] In some embodiments, the lithium phosphate compound may include two or more metals. For example, the lithium phosphate compound may include Ti and other metals other than Ti. For example, the metal different from Ti may be at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W. Specifically, the metal different from Ti may be Al.
[0105] Within the crystal lattice structure of the lithium phosphate compound, since the metal different from Ti substitutes for the Ti site, the migration of lithium ions can be made smoother. Therefore, the coating can have a higher ionic conductivity, and a lithium secondary battery with high efficiency and further improved fast charging characteristics can be provided.
[0106] In some embodiments, the lithium phosphate compound may be represented by Chemical Formula 2 below.
[0107] [Chemical Formula 2]
[0108] Li a (Ti e+ ) x (M1 f+ ) y P d O (a+ex+fy+5d) / 2
[0109] In Chemical Formula 2, M1 may be at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W.
[0110] a may be 0 < a ≤ 5, x may be 0 < x ≤ 1, y may be 0 < y < 5, d may be 0 < d ≤ 8, and 1 ≤ x + y ≤ 5 may hold. e is an integer representing the oxidation state of Ti, and e may be 1 ≤ e ≤ 4. f is an integer representing the oxidation state of M1, and f may be 1 ≤ f ≤ 5.
[0111] Figure 1 and Figure 2 are process flowcharts for explaining a method for preparing a positive electrode active material according to an exemplary embodiment. Hereinafter, with reference to Figure 1 and Figure 2 , the method for preparing the above positive electrode active material will be described.
[0112] With reference to Figure 1 , a coating precursor and a first solvent may be mixed to prepare a first mixture (for example, step S10).
[0113] The coating precursor is a precursor for forming the above coating, and the coating precursor may include a lithium precursor, a coating metal precursor, and a phosphorus precursor.
[0114] For example, the lithium precursor may include lithium carbonate, lithium acetate, lithium phosphate, lithium oxalate, lithium oxide, lithium hydroxide, etc.
[0115] The phosphorus precursor may include orthophosphoric acid, triphosphoric acid, tetraphosphoric acid, trialkyl phosphate, etc.
[0116] In one embodiment, the coated metal precursor may comprise a titanium precursor. For example, a titanium-containing metal salt may be used as the titanium precursor, and the titanium-containing metal salt may include titanium oxide, titanium hydroxide, titanium alkoxide, titanium carbonate, titanium acetate, or their hydrates, etc.
[0117] In some embodiments, the coated metal precursor may comprise more than two coated metal precursors. For example, it may comprise a first coated metal precursor and a second coated metal precursor different from the first coated metal precursor. The first coated metal precursor may be the above-mentioned titanium precursor.
[0118] For example, the second coated metal precursor may comprise a metal different from Ti. For example, it may comprise at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W.
[0119] In one embodiment, the second coated metal precursor may include carbonates, alkoxides, oxides, hydroxides, etc. containing the metal different from Ti. For example, the second coated metal precursor may comprise aluminum. For example, the second coated metal precursor may be an aluminum alkoxide.
[0120] The coated precursors may be mixed in a proportion that satisfies the content or concentration ratio of each metal described with reference to Chemical Formula 1 or Chemical Formula 2.
[0121] In some embodiments, a compound dissolved in the first solvent may be used as the coated precursor. For example, when the first solvent is a polar solvent, the coated precursor may be polar, and when the first solvent is a non-polar solvent, the coated precursor may be non-polar.
[0122] In one embodiment, the coated precursor and the first solvent may be mixed at a speed of 100 rpm to 500 rpm for 1 minute to 20 minutes, and the mixing speed and time may be appropriately adjusted according to the contents of the coated precursor and the first solvent.
[0123] A second solvent may be mixed in the first mixture to prepare a second mixture (e.g., step S20).
[0124] The second solvent may be immiscible with the first solvent. The term "immiscible" used in this application may mean that different types of solvents do not form a homogeneous mixture with each other, and phase separation occurs when one solvent is slowly dropped into the other solvent. For example, "immiscible" may represent the relationship between a polar solvent and a non-polar solvent, or may represent the relationship between a water-soluble solvent and a fat-soluble solvent.
[0125] In some embodiments, the difference between the polarity index of the first solvent and the polarity index of the second solvent can be 4 or more.
[0126] For example, when the first solvent is a polar solvent, the second solvent can be a nonpolar solvent. In this case, the lithium precursor, the coating metal precursor, and the phosphorus precursor can be polar.
[0127] For example, when the first solvent is a nonpolar solvent, the second solvent can be a polar solvent. In this case, the lithium precursor, the coating metal precursor, and the phosphorus precursor can be nonpolar.
[0128] Therefore, since the coating precursor has an electron distribution or dipole moment similar to that of the first solvent, the coating precursor can be selectively dissolved only in the first solvent and can be insoluble in the second solvent having a substantially different polarity.
[0129] The term "nonpolar" or "apolar" used in the present application refers to a state with very little or no polarity and can be used as a concept opposite to polar substances.
[0130] The second solvent can be added to the first mixture and mixed at a speed of 100 rpm to 500 rpm for 1 minute to 20 minutes. Through this mixing, an emulsion of the second solvent can be formed within the second mixture.
[0131] Primary positive electrode active material particles can be mixed in the second mixture to prepare a precursor solution (for example, step S30).
[0132] The primary positive electrode active material particles can serve as core particles of the positive electrode active material. For example, the above-mentioned lithium metal oxide particles can be used as the primary positive electrode active material particles.
[0133] Refer to Figure 2 , the primary positive electrode active material particles can be added to the second mixture (for example, step S31), and the second mixture can be ultrasonically treated (for example, step S32).
[0134] Figure 3 and Figure 4 are schematic diagrams for explaining step S31 and step S32, respectively.
[0135] Refer to Figure 3 , primary positive electrode active material particles 20 can be added to the second mixture.
[0136] In one embodiment, since the first solvent 12 and the second solvent 14 are immiscible, the second mixture can be separated into a layer containing the first solvent 12 and a layer containing the second solvent 14.
[0137] In one embodiment, the second solvent 14 can exist in the form of an emulsion within the first solvent 12. For example, since the second solvent 14 has a different polarity from the first solvent 12, the cohesion of the second solvent 14 can be relatively enhanced, so that it can exist in a condensed form within the first solvent 12.
[0138] Since the coating precursors (30, 35) are insoluble in the second solvent 14, the coating precursors (30, 35) can be selectively dissolved in the first solvent 12. For example, the coating precursors (30, 35) can substantially exist only within the first solvent 12.
[0139] Referring to Figure 4 , the second mixture to which the primary cathode active material particles 20 are added can be subjected to sonication.
[0140] By subjecting the second mixture to sonication, the second solvent 14 can be dispersed within the first solvent 12 to form an emulsion, and can cover the surface of the primary cathode active material particles 20 present within the first solvent 12. Therefore, a thin film 22 containing the second solvent 14 can be formed on the surface of the primary cathode active material particles 20.
[0141] In one embodiment, the sonication can be carried out under conditions of a frequency of 10 kHz to 30 kHz and an intensity of 500 W to 800 W. For example, the sonication can be carried out at a frequency of about 20 KHz and an intensity of about 700 W.
[0142] In one embodiment, the sonication can be carried out in a state where the second mixture is sealed, and the sonication can be carried out for 2 minutes or more, 3 minutes or more, or 5 minutes or more. For example, the sonication can be carried out for 5 minutes to 20 minutes.
[0143] Within the above range, it is possible to prevent the coating precursors present within the first solvent 14 from reacting or precipitating due to the energy of the sonication.
[0144] In the second mixture or the precursor solution, the content of the second solvent can be less than the content of the first solvent. Therefore, the second solvent 14 with a smaller content can form a thin film 22 on the surface of the primary cathode active material particles 20, and the first solvent 12 with a larger content can act as the base solvent of the precursor solution.
[0145] In one embodiment, through the ultrasonic treatment, a first thin film 22 containing a second solvent 14 and a second thin film 24 surrounding the first thin film 22 and containing a first solvent 12 can be formed.
[0146] In one embodiment, in the second mixture or the precursor solution, the content of the first solvent 12 can be more than 2 times the content of the second solvent 14. For example, the content of the first solvent 12 can be more than 3 times, more than 4 times, or more than 4.5 times the content of the second solvent 14. Additionally, the content of the first solvent 12 can be 10 times or less, 9 times or less, or 8 times or less the content of the second solvent 14.
[0147] Within the above range, the second solvent 14 can form a more stable emulsion within the second mixture and can form a more uniform thin film on the surface of the primary cathode active material particles 20 within the precursor solution.
[0148] Therefore, through ultrasonic treatment, a droplet structure of primary cathode active material particles 20, a first thin film 22 containing a second solvent, and a second thin film 24 containing a first solvent can be formed within the precursor solution.
[0149] For example, when the content of the first solvent is less than 2 times the content of the second solvent, even with ultrasonic treatment, the first solvent and the second solvent within the precursor solution may exist in a phase-separated state. Therefore, it may not be possible to form a thin film containing the second solvent on the primary cathode active material particles 20.
[0150] Furthermore, when the content of the first solvent is much greater than the content of the second solvent, the second solvent may be substantially miscible in the first solvent, and thus it may not be possible to form an emulsion within the second mixture. Therefore, it may not be possible to form a thin film on the primary cathode active material particles 20.
[0151] The precursor solution can be heat-treated to form a coating on the surface of the primary cathode active material particles (e.g., step S40). The coating can contain a lithium phosphate compound.
[0152] According to an exemplary embodiment, the precursor solution can be heated to a first temperature to evaporate the second solvent (e.g., step S41), and then heated to a second temperature higher than the first temperature to evaporate the first solvent (e.g., step S42).
[0153] In some embodiments, the boiling point of the first solvent can be higher than the boiling point of the second solvent. Therefore, the first solvent and the second solvent can be selectively evaporated.
[0154] The first temperature may be higher than or equal to the boiling point of the second solvent and lower than the boiling point of the first solvent. Thus, by heating to the first temperature, only the second solvent can be evaporated, and the first solvent can remain in the precursor solution.
[0155] The second temperature may be higher than or equal to the boiling point of the first solvent. Thus, by heating to the second temperature, the first solvent can be evaporated, and the coating precursor dissolved in the first solvent can form a coating on the surface of the primary cathode active material particles.
[0156] For example, through the heat treatment step, the coating precursors can react with each other to form a lithium phosphate compound. Due to the evaporation of the first solvent, the lithium phosphate compound can form a coating on the primary cathode active material particles.
[0157] By selectively evaporating the first solvent and the second solvent, the uniformity of the coating can be further improved. For example, as the first thin film surrounding the primary cathode active material particles is gradually removed, the coating precursor dissolved in the second thin film can uniformly cover the surface of the primary cathode active material particles.
[0158] After that, by evaporating the first solvent, the coating precursors uniformly covering the surface of the primary cathode active material particles can react to form a lithium phosphate compound, and a uniform coating can be formed on the surface of the primary cathode active material particles.
[0159] In one embodiment, the difference between the first temperature and the boiling point of the second solvent may be 10 °C or less or 5 °C or less. The difference between the second temperature and the boiling point of the first solvent may be 10 °C or less or 5 °C or less. Thus, the evaporation rates of the second solvent and the first solvent can be appropriately adjusted, and the coating uniformity can be further improved.
[0160] In some embodiments, the heat treatment process may be carried out at a pressure of 500 millibars (mbar) to 1000 millibars.
[0161] In some embodiments, the obtained cathode active material can be further subjected to a calcination process to remove the residual solvent and improve the crystallinity of the coating.
[0162] In one embodiment, the calcination temperature may be in the range of about 150 °C to 600 °C, or may be in the range of 200 °C to 400 °C. The calcination can be carried out for more than 30 minutes. For example, the calcination time can be 1 hour to 2 hours.
[0163] According to an exemplary embodiment, by forming a coating on the positive electrode active material particles using different types of immiscible solvents under specified process conditions, the coating uniformity can be improved. Accordingly, the initial efficiency and high-rate characteristics of the lithium secondary battery can be improved, and the life characteristics can be enhanced due to high reaction stability and low electronic conductivity.
[0164] <Lithium secondary battery>
[0165] The lithium secondary battery according to an exemplary embodiment may include a positive electrode composite and a negative electrode, the positive electrode composite including the above-described positive electrode active material, and the negative electrode being disposed opposite to the positive electrode composite.
[0166] The positive electrode composite may include the above-described positive electrode active material, a solid electrolyte, and a conductive material. For example, the positive electrode active material may be mixed and stirred with the solid electrolyte, the conductive material, and / or a binder, etc. to prepare a primary positive electrode composite, and the primary positive electrode composite may be pressed to prepare the positive electrode composite.
[0167] According to one embodiment, a sulfide-based electrolyte may be used as the solid electrolyte.
[0168] For example, the sulfide-based solid electrolyte may be represented by Chemical Formula 4.
[0169] [Chemical Formula 4]
[0170] Li e Y f P g S h Z i
[0171] In Chemical Formula 4, e may be 0 < e < 12, f may be 0 ≤ f ≤ 6, g may be 0 ≤ g ≤ 6, h may be 0 ≤ h ≤ 12, i may be 0 ≤ i ≤ 9, Y may be at least one element selected from B, Al, Ga, In, Si, Ge, Sn, Pb, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, and W, and Z may be at least one element selected from F, Cl, Br, and I.
[0172] In some embodiments, the sulfide-based solid electrolyte may be an LPS-based solid electrolyte including Li, P, and S, an LGPS-based solid electrolyte including Li, P, Ge, and S, or an LSiPSCl-based solid electrolyte including Li, Si, P, S, and Cl.
[0173] For example, the sulfide-based solid electrolyte may use Li2S-P2S5, Li10 GeP2S 12 、Li 10 SnP2S 12 、Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li 10 (Ge 0.5 Sn 0.5 )P2S 12 、Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li 10 GeP2S 11.7 O 0.3 、Li 9.6 P3S 12 、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 、Li 10.35 Si 1.35 P 1.65 S 12 、Li 9.81 Sn 0.81 P 2.19 S 12 、Li 9.42 Si 1.02 P 2.1 S 9.96 O 2.04 、Li6PS5Cl, etc.
[0174] The conductive material may be included to facilitate electron migration between the positive electrode active material particles. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, graphene, carbon nanotubes, etc. and / or metal-based conductive materials including perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, etc.
[0175] In some embodiments, the primary cathode composite may further comprise a binder. For example, the binder may include poly(vinylidene fluoride - hexafluoropropylene) copolymer (PVDF - co - HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, nitrile butadiene rubber, etc.
[0176] In an exemplary embodiment, the primary cathode composite may be pressed to form a cathode composite. The pressing process may be carried out by flat pressing in the form of uniaxial pressing or isostatic pressing in the form of triaxial pressing.
[0177] In one embodiment, the pressing may be an isostatic pressing process. For example, the pressing may be carried out by hot pressing (warm isostatic press, WIP), cold pressing (cold isostatic press, CIP), or roll pressing process.
[0178] In one embodiment, the pressing may be carried out by a cold pressing (CIP) process. The primary cathode composite may be placed in a packaging material and sealed, and then pressed and formed by a cold pressing process (e.g., cold isostatic pressing (CIP)). In this case, compared with flat pressing, the stress acts uniformly in all directions, thereby suppressing the bending phenomenon of the cathode composite.
[0179] In one embodiment, the pressing may be carried out at a pressure of 200 MPa to 800 MPa for 10 seconds to 1 minute. For example, the pressing may be carried out at a pressure of 300 MPa to 600 MPa for 10 seconds to 40 seconds. Within the above range, the adhesion between the cathode active material particles and the solid electrolyte can be improved.
[0180] The anode may be used in the form of an anode composite formed by pressing the anode active material and the solid electrolyte or in the form of the anode active material. In the case of pressing, it may be carried out by flat pressing in the above - mentioned pressing form or isostatic pressing in the form of triaxial pressing.
[0181] The negative electrode active material can be a material known in the art that allows lithium ions to be intercalated and deintercalated without particular limitation. For example, the negative electrode active material can be a carbon-based material such as crystalline carbon, amorphous carbon, carbon composite, carbon fiber, etc.; a lithium alloy; silicon or tin, etc. Examples of the amorphous carbon can include hard carbon, coke, mesocarbon microbead (MCMB) calcined at 1500 °C or lower, mesophase pitch-based carbon fiber (MPCF), etc. Examples of the crystalline carbon can include natural graphite, graphitized coke, graphitized MCMB, graphitized MPCF, etc., which are graphite-based carbons. Examples of the elements contained in the lithium alloy can include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium, etc.
[0182] The positive electrode composite and the negative electrode composite belonging to each battery cell can respectively include a positive electrode current collector and a negative electrode current collector.
[0183] The positive electrode current collector can include stainless steel, nickel, aluminum, titanium, copper, or their alloys, etc. For example, it can include aluminum or aluminum alloy.
[0184] The negative electrode current collector can include gold, stainless steel, nickel, aluminum, titanium, copper, or their alloys, etc. For example, it can include copper or copper alloy.
[0185] The tabs (positive electrode tab and negative electrode tab) can respectively protrude from the positive electrode current collector and the negative electrode current collector and extend to one side of the housing of the secondary battery. The tabs can be fused to the one side of the housing and form electrode leads (positive electrode lead and negative electrode lead) that extend to the outside of the housing or are exposed outside the housing.
[0186] According to an exemplary embodiment, a solid electrolyte layer can be provided between the positive electrode composite and the negative electrode composite.
[0187] In one embodiment, the solid electrolyte layer can include a sulfide-based solid electrolyte. The sulfide-based electrolyte can be the same as or different from the sulfide-based solid electrolyte contained in the positive electrode composite.
[0188] The solid electrolyte layer can include an LPS-based solid electrolyte, an LGPS-based solid electrolyte, or an LSiPSCl-based solid electrolyte. For example, the solid electrolyte layer can use Li2S-P2S5, Li 10 GeP2S 12 、Li 10 SnP2S 12 、Li 9.54 Si 1.74 P 1.44 S11.7 Cl 0.3 、Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li 10 (Ge 0.5 Sn 0.5 )P2S 12 、Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li 10 GeP2S 11.7 O 0.3 、Li 9.6 P3S 12 、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 、Li 10.35 Si 1.35 P 1.65 S 12 、Li 9.81 Sn 0.81 P 2.19 S 12 、Li 9.42 Si 1.02 P 2.1 S 9.96 O 2.04 、Li6PS5Cl, etc.
[0189] According to an exemplary embodiment, the cell can be defined by a positive electrode composite, a negative electrode composite, and a solid electrolyte layer, and an electrode assembly can be formed by stacking a plurality of the cells. For example, the electrode assembly can be formed by winding, laminating, folding, etc.
[0190] The electrode assembly can be housed in a casing, thereby defining a lithium secondary battery. The lithium secondary battery can be made, for example, in a cylindrical, prismatic, pouch type, coin type, etc. using a can.
[0191] Hereinafter, to help understand the present invention, preferred embodiments are presented, but these embodiments are only for illustrating the present invention and are not used to limit the scope of the claims. Various changes and modifications can be made to the embodiments within the scope and technical idea of the present invention, which is obvious to those skilled in the art, and such variations and modifications also belong to the scope of the claims as a matter of course.
[0192] Preparation Example
[0193] (1) Preparation of primary cathode active material particles
[0194] Using distilled water that has been bubbled with N2 for 24 hours to remove internal dissolved oxygen, NiSO4, CoSO4, and MnSO4 are mixed in a ratio of 88:9:3 respectively. The above solution is added to a reactor at 50 °C, and NaOH and NH3·H2O are used as precipitants and chelating agents for coprecipitation reaction for 48 hours to obtain Ni 0.88 Co 0.09 Mn 0.03 (OH)2. The obtained precursor is dried at 80 °C for 12 hours and then dried again at 110 °C for 12 hours.
[0195] Lithium hydroxide and the transition metal precursor are added to a dry high-speed mixer in a ratio of 1.01:1 to 1.025:1 and mixed evenly for 5 minutes. The above mixture is placed in a calcination furnace, heated to 730 °C to 750 °C at a heating rate of 2 °C / minute, and maintained at 730 °C to 750 °C for 10 hours. During heating and maintaining, oxygen is continuously introduced at a flow rate of 10 mL / minute. After calcination, it is naturally cooled to room temperature, and then pulverized and classified to obtain the primary cathode active material particles of LiNi 0.88 Co 0.09 Mn 0.03 O2 (D 50 : 10 μm).
[0196] (2) Preparation of cathode active material
[0197] Example 1
[0198] Mix 2.1 mg of lithium acetate as a lithium precursor, 2.18 mg of aluminium ethoxide as a transition metal precursor, 11.3 μL of titanium ethoxide, and 18 μL of triethyl phosphate as a phosphate compound.
[0199] After that, add 10 ml of acetonitrile as the first solvent and stir at 300 rpm for 10 minutes to obtain the first mixture.
[0200] Add 2 ml of hexane as the second solvent to the first mixture obtained above and stir at 300 rpm for 10 minutes to obtain the second mixture. Add 5 g of LiNi 0.88 Co0.09 Mn 0.03 O2 particles, and the mixed solution is ultrasonically treated to obtain a dispersion.
[0201] In the ultrasonic treatment, while sealing the second mixture, a tower ultrasonic crusher (STH-750S) is used, and the ultrasonic treatment is carried out for 5 to 10 minutes under the conditions of a frequency of 20 KHz and a power of 700 W.
[0202] The dispersion prepared above is added to a rotary evaporation concentrator (R-100, manufactured by Buchi), and the vacuum degree of the rotary evaporation concentrator is set to about 800 mbar. The temperature of the oil bath of the rotary evaporation concentrator is raised to about 69 °C to evaporate hexane, and then raised to 83 °C again to evaporate acetonitrile.
[0203] After that, heat treatment is carried out at a temperature of 280 °C for 1 hour to remove the residual solvent, and a coating of LiTi 0.88 Co 0.09 Mn 0.03 O2 particles is formed on the 1.6 Al 0.4 (PO4)3 crystal phase to obtain the positive electrode active material particles according to Example 1.
[0204] Example 2
[0205] The positive electrode active material particles according to Example 2 are prepared by the same method as in Example 1, except that 7 ml of acetonitrile as the first solvent and 5 ml of hexane as the second solvent are added.
[0206] Example 3
[0207] The positive electrode active material particles according to Example 3 are prepared by the same method as in Example 1, except that 11 ml of acetonitrile as the first solvent and 1 ml of hexane as the second solvent are added.
[0208] Comparative Example 1
[0209] 2.1 mg of lithium acetate as a lithium precursor, 2.18 mg of aluminium ethoxide as a transition metal precursor, 11.3 μL of titanium ethoxide, and 18 μL of triethyl phosphate as a phosphate compound are mixed.
[0210] Thereafter, 12 ml of ethanol as a solvent was added and stirred at 300 rpm for 10 minutes to prepare a mixture. 5 g of the above-prepared LiNi 0.88 Co 0.09 Mn 0.03 O2 particles were added, and ultrasonic treatment was performed in the same manner as in Example 1 to prepare a dispersion.
[0211] The above-prepared dispersion was added to a rotary evaporator (R-100, manufactured by BUCHI), the vacuum degree of the rotary evaporator was set to about 800 mbar, and the temperature of the oil bath of the rotary evaporator was raised to about 79 °C to evaporate ethanol. Thereafter, heat treatment was performed at 280 °C for 1 hour to remove the residual solvent, thereby obtaining the positive electrode active material particles according to Comparative Example 1.
[0212] Comparative Example 2
[0213] The positive electrode active material particles according to Comparative Example 2 were obtained by the same method as in Comparative Example 1, except that 12 ml of acetonitrile was added as a solvent instead of ethanol, and the temperature of the oil bath of the rotary evaporator was raised to about 83 °C.
[0214] Comparative Example 3
[0215] The positive electrode active material particles according to Comparative Example 3 were obtained by the same method as in Comparative Example 1, except that 2 ml of hexane was added as a solvent instead of ethanol, and the temperature of the oil bath of the rotary evaporator was raised to about 69 °C.
[0216] Comparative Example 4
[0217] The positive electrode active material particles according to Comparative Example 4 were prepared by the same method as in Example 1, except that 10 ml of acetonitrile as a first solvent was added, and 2 ml of ethanol as a second solvent was added.
[0218] Experimental Example 1
[0219] (1) Measurement of Coating Thickness
[0220] TEM analysis was performed on the cross-section of the above-prepared positive electrode active material particles using a transmission electron microscope (Tecnai G2 F30, manufactured by FEI) to measure the coating thickness. The thickness of the thickest coating formed on the positive electrode active material particles was measured as the maximum coating thickness, and the thickness of the thinnest coating formed on the positive electrode active material particles was measured as the minimum coating thickness.
[0221] The coating thickness deviation is calculated as the value obtained by subtracting the minimum thickness of the measured coating from the maximum thickness of the coating. The evaluation results are recorded in Table 1 below.
[0222] In Table 1 below, "-" indicates a case where the coating thickness could not be measured.
[0223] In the case of Comparative Example 2 and Comparative Example 3, a coating in the shape of a film covering the surface of the positive electrode active material particles was not formed, and a coating in the shape of an island was formed only in a partial region on the particle surface. Therefore, in the case of Comparative Example 2 and Comparative Example 3, since a uniform coating was not formed, the minimum thickness and the maximum thickness of the coating could not be measured.
[0224] The measurement results are shown in Table 2 below.
[0225] (2) Measurement of coating coverage
[0226] The positive electrode active material particles prepared above were analyzed by SEM and Energy Dispersive Spectrometer (EDS) using a scanning electron microscope (FEI Company, Nova nano SEM 450) to measure the distribution of Ti element on the surface of the positive electrode active material particles. Specifically, based on the EDS mapping image of the positive electrode active material surface, the area of the region occupied by the Ti element was calculated to measure the Ti element distribution.
[0227] The Ti element distribution measured in the positive electrode active material particles of Example 1 was set to 1, and the relative value of the Ti element distribution measured in the positive electrode active material particles of other Examples and Comparative Examples was calculated.
[0228] The measurement results are shown in Table 1 below.
[0229] [Table 1]
[0230]
[0231] Referring to Table 1 above, it can be confirmed that in the positive electrode active material according to the Examples, since different types of immiscible solvents were used to form the coating, the coating uniformity was improved.
[0232] However, in Comparative Example 1 where only a single solvent was used, a non-uniform coating was formed and the deviation of the coating thickness in each region increased. In addition, in Comparative Example 2 and Comparative Example 3, the coating coverage was low and the coating was formed only in a partial region, so the coating thickness could not be measured.
[0233] In Comparative Example 3 using a solvent in which the coating substance is insoluble, almost no coating was formed on the surface of the positive electrode active material particles. In the case of Comparative Example 4 using different types of mutually soluble solvents, a decrease in coating uniformity was confirmed.
[0234] Figure 5 is a TEM image of the positive electrode active material particles according to Example 1. Figure 6 is a TEM image of the positive electrode active material particles according to Comparative Example 1.
[0235] See Figure 5 , it can be confirmed that a uniform coating was formed on the surface of the positive electrode active material particles according to Example 1.
[0236] See Figure 6 , it can be confirmed that the positive electrode active material particles according to Comparative Example 1 contain an uneven coating, and there is a large deviation in the coating thickness according to the regions on the particle surface.
[0237] Experimental Example 2
[0238] (1) Fabrication of Lithium Secondary Battery
[0239] A secondary battery was fabricated using the above-prepared positive electrode active material. Specifically, the positive electrode active materials of the examples and comparative examples, a solid electrolyte (Li6PS5Cl), and a conductive material (Super P) were mixed at a mass ratio of 68:29.1:2.91, respectively, to obtain a positive electrode composite.
[0240] The solid electrolyte (Li6PS5Cl) with a density of 10 mg / cm 2 was placed in a stainless steel (SUS) circular mold with a diameter of Φ13 and uniaxially cold isostatically pressed (CIP) at 80 MPa to obtain solid electrolyte pellets. The positive electrode composite was placed on one side of the solid electrolyte pellets at 10 mg / cm 2 and pelletized by pressing at 350 MPa, and then an In foil was placed on the other side and pressed at 50 MPa to obtain an electrode assembly having a structure of positive electrode composite - solid electrolyte - In negative electrode. The electrode assembly was assembled inside the outer packaging material of a coin-type battery with a diameter of Φ20.
[0241] (2) Evaluation of Initial Efficiency
[0242] At 30 °C, the coin-type battery prepared above was charged (CC-CV 0.1C, 4.3V, cut-off at 0.01C) and discharged (CC 0.1C, cut-off at 2.5V), and the initial charge capacity and initial discharge capacity were measured. As shown in Equation 2 below, the initial efficiency was evaluated as the percentage of the initial discharge capacity (A2) relative to the initial charge capacity (A1).
[0243] [Equation 2]
[0244] Initial efficiency (%) = A2 / A1 × 100%
[0245] The evaluation results were recorded in Table 2 below.
[0246] (3) Evaluation of high-rate characteristics
[0247] At a temperature of 30 °C, for the coin-type battery prepared above, according to the charge-discharge cycle with a cut-off charge of 4.3V and a cut-off discharge of 2.5V, the first 3 cycles were charged and discharged at 0.1C, and the discharge capacity (B1) of the first cycle was measured. Thereafter, the battery was charged and discharged at a rate of 0.2C for 2 cycles, and charged and discharged at a rate of 0.5C for 2 cycles. Thereafter, the battery was charged and discharged at 1C, and the discharge capacity (B2) was measured.
[0248] As shown in Equation 3 below, the high-rate characteristics were evaluated as the percentage of the discharge capacity (B2) at a high rate (1C) relative to the discharge capacity (B1) at a low rate (0.1C).
[0249] [Equation 3]
[0250] High-rate characteristics (%) = B2 / B1 × 100%
[0251] The evaluation results were recorded in Table 2 below.
[0252] [Table 2]
[0253]
[0254] Referring to Table 1 and Table 2, in the case of the secondary battery according to the embodiment, the deviation of the coating thickness of the positive electrode active material particles is small, and high initial efficiency and high-rate charging characteristics are exhibited.
[0255] However, in the case of the secondary battery according to the comparative example, the initial efficiency is generally low, and the high-rate charging characteristics are reduced.
[0256] In the cases of Comparative Example 1 and Comparative Example 4, the coating coverage rate of the positive electrode active material particles is high, but the deviation of the coating thickness is large. Therefore, compared with the examples, the charging characteristics and efficiency at high rates are reduced.
[0257] In the case of Comparative Example 2 and Comparative Example 3, no coating was formed on the surface of the positive electrode active material particles or the coating coverage rate was low, and the high-rate charging characteristics were significantly reduced. Moreover, due to the low ionic conductivity, a low initial efficiency was exhibited.
[0258] In the case of the Examples, when preparing the coating, different types of immiscible solvents were used and the specified process conditions were satisfied, so that a thin and uniform coating was formed.
Claims
1. A positive electrode active material, comprising: a core particle; and a coating formed on the surface of the core particle, and the coating contains a lithium phosphate compound containing a transition metal, Among them, the difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating is 17 nm or less.
2. The positive electrode active material according to claim 1, wherein, The difference between the maximum thickness and the minimum thickness of the coating measured on the cross-section of the coating is 0.1 nm to 10 nm.
3. The positive electrode active material according to claim 1, wherein, The thickness of the coating is 1 nm to 50 nm.
4. The positive electrode active material according to claim 1, wherein, The positive electrode active material satisfies the following formula 1, [Formula 1] (|T M -T E | / T E )×100 ≤ 20 In the formula 1, T E is the average thickness value of the coating, and T M is either the maximum thickness or the minimum thickness of the coating.
5. The positive electrode active material according to claim 1, wherein, Based on 100 parts by weight of the core particle, the content of the coating is 0.1 part by weight to 1 part by weight.
6. The positive electrode active material according to claim 1, wherein, The lithium phosphate compound contains titanium and other metals different from titanium.
7. The positive electrode active material according to claim 1, wherein The coating contains a compound represented by the following Chemical Formula 1, [Chemical Formula 1] Li a (M b+ ) c P d O (a+bc+5d) / 2 In Chemical Formula 1, M is at least one selected from Ti, B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W, and 0 < a ≤ 5, 1 ≤ b ≤ 5, 1 ≤ c ≤ 5, 0 < d ≤ 8.
8. The positive electrode active material according to claim 1, wherein, The coating contains a compound represented by the following Chemical Formula 2, [Chemical Formula 2] Li a (Ti e+ ) x (M1 f+ ) y P d O (a+ex+fy+5d) / 2 In Chemical Formula 2, M1 is at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W, and 0 < a ≤ 5, 1 ≤ e ≤ 4, 1 ≤ f ≤ 5, 0 < x ≤ 1, 0 < y < 5, 1 ≤ x + y ≤ 5, 0 < d ≤ 8.
9. The positive electrode active material according to claim 1, wherein, The average particle size D of the nuclear particles 50 is from 1 μm to 12 μm.
10. A lithium secondary battery, comprising: a positive electrode containing the positive electrode active material according to claim 1 and a solid electrolyte; a negative electrode disposed opposite to the positive electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode.
11. A method for preparing a positive electrode active material, comprising the following steps: preparing a first mixture containing a lithium precursor, a coating metal precursor, a phosphorus precursor, and a first solvent; mixing a second solvent immiscible with the first solvent in the first mixture to prepare a second mixture; adding primary positive electrode active material particles to the second mixture to prepare a precursor solution; and performing a heat treatment on the precursor solution to form a coating containing a lithium phosphate compound on the surface of the primary positive electrode active material particles.
12. The method for preparing the positive electrode active material according to claim 11, wherein, The lithium precursor, the coating metal precursor, and the phosphorus precursor are respectively dissolved in the first solvent and insoluble in the second solvent.
13. The method for preparing the positive electrode active material according to claim 11, wherein, The coating metal precursor includes a first coating metal precursor and a second coating metal precursor, and the first coating metal precursor is a titanium precursor.
14. The method for preparing the positive electrode active material according to claim 11, wherein, The lithium phosphate compound contains a compound represented by the following Chemical Formula 2, [Chemical Formula 2] Li a (Ti e+ ) x (M1 f+ ) y P d O (a+ex+fy+5d) / 2 In Chemical Formula 2, M1 is at least one selected from B, Al, Y, Sc, Zr, V, Nb, Ta, Cr, Ga, Sn, Sb, and W, and 0 < a ≤ 5, 1 ≤ e ≤ 4, 1 ≤ f ≤ 5, 0 < x ≤ 1, 0 < y < 5, 1 ≤ x + y ≤ 5, 0 < d ≤ 8.
15. The method for preparing a positive electrode active material according to claim 11, wherein, The difference between the polarity index of the first solvent and the polarity index of the second solvent is 4 or more.
16. The method for preparing a positive electrode active material according to claim 11, wherein, In the precursor solution, the content of the second solvent is less than the content of the first solvent.
17. The method for preparing the positive electrode active material according to claim 11, wherein, Before heat-treating the precursor solution, it further includes a step of ultrasonically treating the precursor solution.
18. The method for preparing the positive electrode active material according to claim 17, wherein, By the step of ultrasonically treating the precursor solution, a first thin film containing the second solvent is formed on the primary cathode active material, and a second thin film containing the first solvent is formed on the first thin film.
19. The method for preparing the positive electrode active material according to claim 11, wherein, The step of heat-treating the precursor solution includes the following steps: heating the precursor solution to a first temperature to evaporate the second solvent, and heating to a second temperature higher than the first temperature to evaporate the first solvent.
20. The method for preparing a positive electrode active material according to claim 19, wherein, The boiling point of the first solvent is higher than the boiling point of the second solvent, the first temperature is higher than or equal to the boiling point of the second solvent and lower than the boiling point of the first solvent, and the second temperature is higher than or equal to the boiling point of the first solvent.
Citation Information
Patent Citations
An electrode for an all solid type battery and a method for manufacturing the same
KR1020180125408A
Cited By
Electrolyte, preparation method thereof and lithium ion battery
CN121642145A